Shikonin Alleviates Gentamicin-Induced Renal Injury in Rats by Targeting Renal Endocytosis, SIRT1/Nrf2/HO-1, TLR-4/NF-κB/MAPK, and PI3K/Akt Cascades - Mohamed F. Balaha; Ahmed A. Alamer; Alaa A. Eisa; Hashim M. Aljohani (MDPI AG, 2023)
Gentamicin causes kidney injury due to its accumulation in proximal tubule epithelial cells via the megalin/cubilin/CLC-5 complex. Recently, shikonin has been shown to have potential anti-inflammatory, antioxidant, antimicrobial, and chloride channel-inhibiting effects. The current study investigated the alleviation of gentamicin-induced renal injury by shikonin while preserving its bactericidal effect. Nine-week-old Wistar rats were administered 6.25, 12.5, and 25 mg/kg/day shikonin orally, one hour after the i.p. injection of 100 mg/kg/day gentamicin for seven days. Shikonin significantly and dose-dependently alleviated gentamicin-induced renal injury, as revealed by restoring normal kidney function and histological architecture. Furthermore, shikonin restored renal endocytic function, as indicated by suppressing the elevated renal megalin, cubilin, and CLC-5 and enhancing the reduced NHE3 levels and mRNA expressions induced by gentamicin. These potentials could be attributed to the modulation of the renal SIRT1/Nrf2/HO-1, TLR-4/NF-κB/MAPK, and PI3K/Akt cascades, which enhanced the renal antioxidant system and suppressed renal inflammation and apoptosis, as indicated by enhancements of SIRT1, Nrf2, HO-1, GSH, SOD, TAC, Iκb-α, Bcl-2, PI3K, and Akt levels and mRNA expressions, with reduction of TLR-4, NF-κB, MAPK, IL-1β, TNF-α, MDA, iNOS, NO, cytochrome c, caspase-3, Bax levels, and Bax/Bcl-2 ratio. Therefore, shikonin is a promising therapeutic agent for alleviating gentamicin-induced renal injury.